Coupled network of the circadian clocks: a driving force of rhythmic physiology. Issue 17 (20th August 2020) - Finger, Anna‐Marie; Dibner, Charna; Kramer, Achim
Abstract : The circadian system is composed of coupled endogenous oscillators that allow living beings, including humans, to anticipate and adapt to daily changes in their environment. In mammals, circadian clocks form a hierarchically organized network with a 'master clock' located in the suprachiasmatic nucleus of the hypothalamus, which ensures entrainment of subsidiary oscillators to environmental cycles. Robust rhythmicity of body clocks is indispensable for temporally coordinating organ functions, and the disruption or misalignment of circadian rhythms caused for instance by modern lifestyle is strongly associated with various widespread diseases. This review aims to provide a comprehensive overview of our current knowledge about the molecular architecture and system‐level organization of mammalian circadian oscillators. Furthermore, we discuss the regulatory roles of peripheral clocks for cell and organ physiology and their implication in the temporal coordination of metabolism in human health and disease. Finally, we summarize methods for assessing circadian rhythmicity in humans. Abstract :